Determination of formation enthalpies of inter-metallic compounds of the system Cr-Ga by calorimetry - Benmachiche, Messaoud; Bensaada, Said (Journal of Applied Engineering Science & Technology; Vol 4 No 2 (2018): Issue In Progress, 2018)
The knowledge of the thermodynamic values of formation (δfH, δfS, δfG ...) of the different phases, likely to appear in an alloy A-B, makes possible to build the equilibrium diagram of the studied system. The experimental data, obtained from the samples of the Cr-Ga system, are used to determine the enthalpies of formation of the alloys of this system by the calorimetric method. The enrichment of a liquid gallium bath, by falling chromium samples, allowed us to determine the formation enthalpy of the CrGa4 alloy by extrapolation of the straight part of δfH. The latter is found of the order of 22100 J / mole.